Implementasi Projek Penguatan Profil Pelajar Pancasila (P5) dalam Mata Pelajaran PJOK di SMA Negeri Se-Kabupaten Bojonegoro - Romadhona Dwi Novitasari; Nanik Indahwati (Departement of Mathematics Education, 2024)
The Pancasila Student Profile Strengthening Project (P5) is a scientific field to observe and overcome student problems. Furthermore, to strengthen the character values ​​in the Pancasila student profile, students are expected to gain more active, interactive, situational, and direct experiences in everyday life. Inconsistent implementation of P5 can lead to uneven results across schools and districts. This research aims to determine the implementation of P5 in PJOK subjects in public high schools throughout Bojonegoro Regency and to identify the obstacles faced in implementing P5 in PJOK subjects. The research method used in research is quantitative descriptive research. The techniques used are interviews, questionnaires, and documentation. Based on the results of the study and discussions that have been carried out, it is concluded that implementing P5 students in PJOK subjects in public high schools in Bojonegoro province is in the